Biodiversity and Potential Use of Macro Algae in Pesisir Barat Lampung - Triana Asih; Muhammad Khayuridlo; Rasuane Noor; Muhfahroyin Muhfahroyin (Biosaintifika: Journal of Biology & Biology Education, 2019)
Pesisir Barat Regency in Lampung has abundant marine biological wealth that has not been widely known and utilized by the community, one of them is macro algae. The objectives of the research were to identify the types of macro algae and to explains the potential use of macro algae in the Pesisir Barat Lampung Region. The study used cruise method. The findings were identified by experts to validate the results of classification, morphology, and qualitative studies regarding the potential use and benefits of macro algae. From the results of this study, 15 species of macro algae were found on Tanjung Setia Beach included; 3 species of green algae (Chlorophyta) consist of Halimeda opuntia L., Caulerpa racemosa F., Ulva lactuca L .; 7 species of brown algae (Phaeophyta) consist of Padina pavonica L., Padina australis H., Sargassum vulgare C.A., Sargassum polycystum C.A., Turbinaria ornata J.A., Turbinaria ornata J.A., Fucus vesiculosus L.; and 5 species of red algae (Rhodophyta), consist of Corallina officinalis L., Gigartina pistilla S., Gigartina disticha S., Gracilaria verrucosa, H., Rhodymenia pseudopalmat J.V.L.The benefits of this research for society to provide insight into the potential use of macro algae which can be utilized in many fields. For students, provide information on the biodiversity of macro algae in the sea.